Barriers to implementing sustainability experienced by middle managers in the fast-moving consumer goods and retail sector - Mountfield, Andrew (Edward Elgar Publishing, 2021)
In order for organisations to develop and embed sustainability, managers must address the different aspects during the strategic decision-making process and incorporate them into their corporate, business and functional level strategies. While it is recognised that middle managers (MMs) play a key role in an organisation's strategy execution in general, little empirical research has been devoted to perceived barriers hindering implementation and how these have impact on agency, and there is a paucity of data that sheds light on how leadership structures and behaviours and formal management processes affect this. This initial study conducted interviews with MMs from companies in the Fast-Moving Consumer Goods & Retail sector, an industry particularly affected by the need for speed of delivery, and increasingly focussed on sustainability implementation in response to changing consumer demands and heightened scrutiny of supply chains. The sector is also characterised by visible external expressions of sustainability commitment. This paper addresses the question: To what degree, do MM experience barriers to this public commitment to sustainability when explicitly or implicitly charged with the integration of sustainability into the day-to-day decision making. The conclusions propose three classes of barriers that affect sustainability agency around leadership structures and behaviours, formal management processes and the perceived sense of agency of MM across strategy implementation beyond sustainability.